2015
DOI: 10.2217/pmt.15.23
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment in Pain Medicine: From Ancient Remedies to Modern Usage

Abstract: Abstract:Over several millennia, substances have been applied to the skin for treatment of pain. Some ingredients are in current use; others have been discontinued.Mechanisms of action include interactions with nociceptive neural networks and inflammatory processes. Substances must penetrate the stratum corneum barrier and vehicles that enhance penetration have been developed. Topical drugs with links to the past include menthol, capsaicin, some opioids, local anaesthetic agents and non-steroidal anti-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 134 publications
0
14
0
3
Order By: Relevance
“…is useful for stomach cancer, and after bad effects of chemotherapy, Chelidonium is useful for relieving pain of cancer that has metastasised to the liver, Euphorbium relives burning pains of cancer (like Arsenicum) but better from cold applications. 29,30 Every dying person will have different symptoms and needs during the time of their 'end of life'. The family can keep their loved ones more comfortable and go through the stages of the dying process in a more holistic and conscious manner using homeopathic remedies.…”
Section: Scope Of Homoeopathy In Cancer Pain Palliation and End Of Lifementioning
confidence: 99%
“…is useful for stomach cancer, and after bad effects of chemotherapy, Chelidonium is useful for relieving pain of cancer that has metastasised to the liver, Euphorbium relives burning pains of cancer (like Arsenicum) but better from cold applications. 29,30 Every dying person will have different symptoms and needs during the time of their 'end of life'. The family can keep their loved ones more comfortable and go through the stages of the dying process in a more holistic and conscious manner using homeopathic remedies.…”
Section: Scope Of Homoeopathy In Cancer Pain Palliation and End Of Lifementioning
confidence: 99%
“…Currently, capsaicin is used in patients with peripheral neuropathy, especially diabetic, postherpetic neuralgia caused by zoster, muscle and joints pains, rheumatoid arthritis, osteoarthritis and in case of sciatica and brachialgia. Usually, it is administered as an ointment but due to poor absorption through the skin it is more and more often advised to use in a form of sticking plaster in concentration of 0.025% or 0.075% [25][26][27][28][29][30][31]. Moreover, the use of high-doses of capsaicin might rapidly provide therapeutic effects for brachioradial pruritus and notalgia paraesthetica patients with almost no side-effects [32].…”
Section: Analgesic and Anti-inflammatory Activitiesmentioning
confidence: 99%
“…15 Topical application of menthol has long been considered to be an effective treatment for mild-to-moderate pain. 16 Investigators have confirmed the painrelieving effects of topical application of menthol on a variety of conditions including neuropathic pain, 17 knee osteoarthrosis, 18 and carpal tunnel syndrome.…”
Section: Introductionmentioning
confidence: 97%